North american tunneling 2014 proceedings - Davidson, Gregg (Soc For Mining Metallurgy, 2014)
The North American Tunneling Conference is the premier forum to discuss new trends and developments in underground construction in North America. With every conference, the number of attendees and breadth of topics grows. North American Tunneling: 2014 Proceedings reflects the theme for the 2014 conference, "Mission Possible." The authors share new theories, novel innovations, and the latest tools that make what once may have been perceived as impossible, now possible. The authors of 128 papers share the latest case histories, expertise, lessons learned, and real-world applications from aroun
Keywords: Tunneling -- Congresses.; Underground construction -- Congresses.; elektronické knihy; electronic books